Implementation Team Games Tournament Learning Model Based on Wordwall Media to Improve Primary School Students Islamic Religion Education Learning Outcomes - Zakiuddin, Muhammad Naufal; Hidayat, Moch Charis; Asrori, Asrori (Al Ulya: Jurnal Pendidikan Islam, 2025)
One of the factors that causes ineffectiveness in the learning process is monotonous learning, especially in Islamic Religious Education learning. This causes many obstacles to achieving learning goals, such as learning outcomes. This research aims to determine the improvement in student learning outcomes in implementing the Team Games Tournament learning model based on Wordwall media in Islamic Religious Education subjects. The method used in this research is Classroom Action Research (CAR). The target subjects in this research were 30 students in grade 5 at SDN 2 Bakalanpule. In carrying out this research, one pre-cycle stage and two cycle stages were used. The pre-cycle stage uses the lecture method, while the next two cycles use the Team Games Tournament learning model based on Wordwall media. Research is carried out for each cycle to determine the improvement in student learning outcomes through the Team Games Tournament model based on Wordwall media. The results obtained in the pre-cycle were an average student score of 78. Then in the second cycle, the average student score increased but was still relatively low, namely 80. And in the last cycle, the average student score increased quite rapidly, namely by 95, which means student learning outcomes have increased. The conclusion of this research is that applying the Team Games Tournament research model based on Wordwall media can positively improve student learning outcomes. The results of this research indicate that the application of the Team Games Tournament learning model based on Wordwall media can improve student learning outcomes. Therefore, it is recommended that further research be conducted to develop more effective learning models and learning media.